Development of Desmos Application Design Integrated PBL Assisted Liveworksheet Based on Mathematical Literacy in AKM Preperation Efforts - Bulan Nuri; Wirdatul Isnani; Fitri Rizani (Postgraduate, University of Mataram, 2025)
This research aims to develop a learning media using Desmos application integrated with PBL (Problem-Based Learning) assisted by live worksheets based on mathematical literacy in preparation for AKM (Minimum Competency Assessment); and determine the feasibility and practicality of the learning media using Desmos application integrated with PBL assisted by live worksheets based on mathematical literacy in preparation for AKM. The research method used is Research and Development with ADDIE models. The research instrument uses a rating scale for media experts, material experts, practitioners, and students. The results of the development of learning media on quadratic equations obtained a percentage of 95.45% with a very valid category from media experts. Material experts gave a percentage of 93.33% with a very valid category. Practitioners gave a percentage of 94.37% with a very practical category. The results of small group trials of students were declared fit for use, and the results of large group trials obtained a percentage of 39.29% strongly agreed and 57.14% agreed to be interested when using Desmos application media assisted by live worksheets. From the results of the research, the learning media developed is very valid and practical to be used in mathematics learning based on expert validation.